2014
DOI: 10.3928/01477447-20140401-54
|View full text |Cite
|
Sign up to set email alerts
|

Proximally Coated Cementless Bipolar Hemiarthroplasty in Dorr Type C Bone

Abstract: The current study was conducted to examine the clinical and radiographic outcomes of cementless bipolar arthroplasty in patients who had type C bone at the time of the procedure. A total of 87 patients (105 hips) who had type C femora and had undergone cementless bipolar hemiarthroplasty with a proximally coated cementless prosthesis for the treatment of displaced femoral neck fractures at a single institution were reviewed. Patients included 83 women and 4 men who had a mean age of 84 years (range, 72-100 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Previous studies showed favorable results of conventional cementless stems for femoral neck fractures4567). Proximal wedged stems also showed favorable results for osteoporotic bone without signs of early subsidence19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed favorable results of conventional cementless stems for femoral neck fractures4567). Proximal wedged stems also showed favorable results for osteoporotic bone without signs of early subsidence19).…”
Section: Discussionmentioning
confidence: 99%
“…The use of cementless stems for femoral neck fractures has remarkably increased in the last decade23). Previously, full-coated tapered stems or conventional proximal tapered stems showed favorable results for femoral neck fractures4567). However, concerns remain about the use of conventional cementless stems because of thigh pain due to diaphyseal fixation and risk of unexpected bone loss due to the morphology of the stem89).…”
Section: Introductionmentioning
confidence: 99%
“…Uncemented femoral component, regardless of collared or uncollared, can provide primary stability and achieve favorable clinical outcomes in Dorr type C bone [24][25][26]. However, the relationship between IPI and proximal femoral morphology has not been well established.…”
Section: Discussionmentioning
confidence: 99%